2013
DOI: 10.1182/blood-2013-06-501452
|View full text |Cite
|
Sign up to set email alerts
|

JAK2V617F leads to intrinsic changes in platelet formation and reactivity in a knock-in mouse model of essential thrombocythemia

Abstract: The principal morbidity and mortality in patients with essential thrombocythemia (ET) and polycythemia rubra vera (PV) stems from thrombotic events. Most patients with ET/PV harbor a JAK2V617F mutation, but its role in the thrombotic diathesis remains obscure. Platelet function studies in patients are difficult to interpret because of interindividual heterogeneity, reflecting variations in the proportion of platelets derived from the malignant clone, differences in the presence of additional mutations, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(82 citation statements)
references
References 58 publications
4
75
0
3
Order By: Relevance
“…Platelet preparation, culture of bone marrow-derived MKs, proplatelet assays, flow cytometry analysis, and generation of cell lysates for western blot analysis have been described before and are detailed elsewhere 24 and in the supplemental Methods.…”
Section: Platelets and Mk Isolation And Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Platelet preparation, culture of bone marrow-derived MKs, proplatelet assays, flow cytometry analysis, and generation of cell lysates for western blot analysis have been described before and are detailed elsewhere 24 and in the supplemental Methods.…”
Section: Platelets and Mk Isolation And Analysismentioning
confidence: 99%
“…Data processing and analysis were performed as described elsewhere. 24 Gene set enrichment analysis was carried out using Gene Set Enrichment Analysis. 26 Version 4 gene sets of Gene Ontology (GO) molecular function were used with a weighted scoring scheme of the Student t scores.…”
Section: Expression Arrays and Qpcr In Cultured Mksmentioning
confidence: 99%
“…Platelets from JAK2V617F knock-in mice showed increased activation in response to CRP-XL, thrombin, collagen, and fibrinogen. 57 In another model transplanted with JAK2V617F knock-in cells, time to occlusion after FeCl 3 treatment was decreased as compared with controls, but formed thrombi were unstable, which was attributed to reduced levels of GPVI. 58 Analysis of thrombosis in vivo in the GATA-1 low mouse model is precluded by the extreme thrombocytopenia observed in those animals.…”
Section: Org Frommentioning
confidence: 99%
“…Fos is a regulator of TGF-β signaling. 32 Previously Muth et al studied patients with MPN and reported that proplatelet numbers were higher in patients with essential thrombocythemia and pre-fibrotic MF than in controls. 33 Proplatelets were even more abundant in patients with fibrotic MF compared to those with pre-fibrotic MF or essential thrombocythemia.…”
Section: V617fmentioning
confidence: 99%